Live Imaging of Heart Injury in Larval Zebrafish Reveals a Multi-Stage Model of Neutrophil and Macrophage Migration - Kaveh, Aryan; Bruton, Finnius A.; Buckley, Charlotte; Oremek, Magdalena E. M.; Tucker, Carl S.; Mullins, John J.; Taylor, Jonathan M.; Rossi, Adriano G.; Denvir, Martin A. (Frontiers in Cell and Developmental Biology, 2020)
Neutrophils and macrophages are crucial effectors and modulators of repair and regeneration following myocardial infarction, but they cannot be easily observed in vivo in mammalian models. Hence many studies have utilised larval zebrafish injury models to examine neutrophils and macrophages in their tissue of interest. However, to date the migratory patterns and ontogeny of these recruited cells is unknown. In this study, we address this need by comparing our larval zebrafish model of cardiac injury to the archetypal tail fin injury model. Our in vivo imaging allowed comprehensive mapping of neutrophil and macrophage migration from primary haematopoietic sites, to the wound. Early following injury there is an acute phase of neutrophil recruitment that is followed by sustained macrophage recruitment. Both cell types are initially recruited locally and subsequently from distal sites, primarily the caudal haematopoietic tissue (CHT). Once liberated from the CHT, some neutrophils and macrophages enter circulation, but most use abluminal vascular endothelium to crawl through the larva. In both injury models the innate immune response resolves by reverse migration, with very little apoptosis or efferocytosis of neutrophils. Furthermore, our in vivo imaging led to the finding of a novel wound responsive mpeg1+ neutrophil subset, highlighting previously unrecognised heterogeneity in neutrophils. Our study provides a detailed analysis of the modes of immune cell migration in larval zebrafish, paving the way for future studies examining tissue injury and inflammation.